O extremo Oeste de Santa Catarina e o sistema de integração na suinocultura: décadas de 1980 a 2010 - Trentini, Clademir (2019)
This dissertation researched the historical paths taken by pig farming, from colonial pig breeding to the process of agro-industrial integration, started before the 1980s and solidified in the subsequent decades, identifying how farmers / breeders who were not part of the integration system joined the process to create controlled by agro -industries. This process, which linked family farming to agroindustry, was studied with a time frame from the 1980s to the 2010s, as it was the most intense period of transformation. The spatial section, the Far West of Santa Catarina, had as reference the municipalities of Mondaí, Itapiranga and surroundings, a space where the changes involved small farmers. She uses as sources of research the oral testimonies of several producers, documents from public companies of rural extension and materials available in community museums. The process welcomed, but also excluded many creators. The agro-industrial system of breeding served as a divider of pig farming in the far west of Santa Catarina. The different ways of attracting creators to the new way of creating interfered in the socioeconomic conjuncture constituted regionally. Agroindustries brought with them new animals, breeding techniques, planning, productive reorganization and, consequently, exclusion. The traditional trader was involved by the agroindustries or, in other cases, he was excluded from the process because he had his role as intermediary in production occupied by the agro-industry. The production was directed to meet the consumer market and not the needs of producers. The productive dynamics got out of the farmer's control and started to be controlled by the agroindustry and made life difficult for the independent breeder, who insisted on remaining working indivi dually. It concludes that the arguments and strategies used to bring agro-industries closer to the creators had effects over the course of some decades. It also concludes that this process involved and integrated producer / creator, without imposing it.